2006
DOI: 10.1140/epje/i2006-10077-1
|View full text |Cite
|
Sign up to set email alerts
|

Stress transmission in wet granular materials

Abstract: We analyze stress transmission in wet granular media in the pendular state by means of three-dimensional molecular-dynamics simulations. We show that the tensile action of capillary bonds induces a self-stressed particle network organized in two percolating "phases" of positive and negative particle pressures. Various statistical descriptors of the microstructure and bond force network are used to characterize this partition. Two basic properties emerge: 1) the highest particle pressure is located in the bulk … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 53 publications
5
79
0
Order By: Relevance
“…Since effects like liquid and possibly permanent solid bridges are not subject of the present study, we refer to the detailed literature, see Refs. [5,9,19,20,24,68,69,74,87,88,90] and references therein.…”
Section: Normal Contact Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Since effects like liquid and possibly permanent solid bridges are not subject of the present study, we refer to the detailed literature, see Refs. [5,9,19,20,24,68,69,74,87,88,90] and references therein.…”
Section: Normal Contact Modelingmentioning
confidence: 99%
“…[40,91,92] and references therein. The challenge here is to reduce the tremendous amount of information on the contact level, like contact-orientation and -force probability distribution functions [68], to the relevant macroscopic properties related to bulk-moduli, anisotropy and inhomogeneity in the contact network. The quest for a macroscopic constitutive model based on microscopic contact parameters is still ongoing.…”
Section: Related Issues In Briefmentioning
confidence: 99%
“…Although the stress tensor is by definition a macroscopic quantity, it can be shown that an equivalent quantity σ i , called 'particle stress', can be defined for each particle i of a granular packing in static equilibrium [41,42,20]:…”
Section: Bi-percolating Structure Of Self-stressesmentioning
confidence: 99%
“…The morphology of each phase is approximately filamentary with variable thickness and a large interface between them. A detailed analysis of this structure shows that the particles at the interface between the two phases have a weak pressure and the largest negative or positive pressures are located at the heart of each phase [20].…”
Section: Bi-percolating Structure Of Self-stressesmentioning
confidence: 99%
See 1 more Smart Citation